Home mechanical ventilation: legal and bioethical aspects. - Toraldo, Domenico Maurizio (Medicina e Morale, 1999)
The author takes into consideration the legal, organizational, ethical and bioethical aspects concerning patients with severe, chronic, respiratory insufficiency treated with mechanical ventilation. The ethical, technical and organizational problems of home care in these situations are analyzed. The complexity of the home care organization is pointed out since it requires the presence of a technical and nursing team, trained specifically for this purpose. The legal aspects of respiratory home care are illustrated, with particular reference to the pneumologist who prescribes and to the general practitioner who is responsible for the operative aspects of the home care. The new figures in home care are the respiratory rehabilitation therapist and the intensive care pneumologist who are responsible for the management of the patient in home care. The possible medical complications of home mechanical ventilation and maintenance of the ventilation circuits are also illustrated. This organizational model requires the active participation of the patient and his/her relatives who are directly involved in the home care, and the advantages and limits of this model are presented. A psychological portrait of the patient is also presented with all the possible conflicting choices that come from the interaction between man and machine. There is also a discussion about the computerized telemetric (long distance) organizational model of home care which is still in an experimental phase in Italy, and the possible legal medical aspects are pointed out. There are some considerations regarding the principle of autonomy and of beneficence and an attempt to explain that the above mentioned principles are not criteria themselves but should be included, according to the personalistic ethics vision, in the awareness of the human person avoiding the possible risk of euthanasia and/or therapeutic obstinacy. The author concludes by stating that when there is a common agreement (doctor-patient-relatives) to undertake respiratory home care, when technically possible, the risk of home mechanical ventilation becoming chronic should always be countered by the real possibility of a new health equilibrium for the patient.